2002
DOI: 10.1002/mds.1281
|View full text |Cite
|
Sign up to set email alerts
|

Bimanual coordination in Parkinson's disease: Deficits in movement frequency, amplitude, and pattern switching

Abstract: Six patients with idiopathic Parkinson's disease (PD) and six age-matched controls participated in a variety of rhythmic bimanual coordination tasks. The main goal of the task was to perform inphase or antiphase patterns of pronation and supination of the forearms at a specified tempo, and to switch from one pattern to the other upon presentation of a visual cue. The availability of advance information was varied to examine whether deficits would emerge under choice versus pre-cue constraints. In pre-cue condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
19
1
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 45 publications
9
19
1
3
Order By: Relevance
“…Indeed, several studies have demonstrated that bimanual coordination is hampered in PD patients (Brown et al, 1993;Johnson et al, 1998;Almeida et al, 2002;Byblow et al, 2002;Alberts et al, 2004Alberts et al, , 2008Ponsen et al, 2006;Nieuwboer et al, 2009;Stegemoller et al, 2009;Wu et al, 2010;Brown and Almeida, 2011;Almeida and Brown, 2013). These deficits range from the organization and execution of simultaneous and sequential movements of the upper limbs (Schwab et al, 1954;Benecke et al, 1987;Marsden, 1989;Harrington and Haaland, 1991;Klockgether and Dichgans, 1994;Bennett et al, 1995;Weiss et al, 1997;Alberts et al, 1998;Johnson et al, 1998), to decreased degree of phasing accuracy and stability (Swinnen et al, 1997;Johnson et al, 1998;Serrien et al, 2000), and several others.…”
Section: Introductionmentioning
confidence: 95%
“…Indeed, several studies have demonstrated that bimanual coordination is hampered in PD patients (Brown et al, 1993;Johnson et al, 1998;Almeida et al, 2002;Byblow et al, 2002;Alberts et al, 2004Alberts et al, , 2008Ponsen et al, 2006;Nieuwboer et al, 2009;Stegemoller et al, 2009;Wu et al, 2010;Brown and Almeida, 2011;Almeida and Brown, 2013). These deficits range from the organization and execution of simultaneous and sequential movements of the upper limbs (Schwab et al, 1954;Benecke et al, 1987;Marsden, 1989;Harrington and Haaland, 1991;Klockgether and Dichgans, 1994;Bennett et al, 1995;Weiss et al, 1997;Alberts et al, 1998;Johnson et al, 1998), to decreased degree of phasing accuracy and stability (Swinnen et al, 1997;Johnson et al, 1998;Serrien et al, 2000), and several others.…”
Section: Introductionmentioning
confidence: 95%
“…During symmetrical (in-phase) triangle drawing, smaller amplitudes were seen but only symmetrical patterns were used . Smaller amplitudes of movements were found predominantly with increasing the frequency from below to above the spontaneous transition frequency (Byblow et al, 2002). More variable amplitude was seen across all conditions for individuals with PD (Serrien et al, 2000).…”
Section: Timing During Sequential Upper Limb Movementsmentioning
confidence: 84%
“…movements. These techniques vary in the specific aspect of motor function measured, and include grip and load force variation (Fellows and Noth, 2004;Guo et al, 2004;Hejdukova et al, 2003;Hermsdorfer, 2002, 2006), finger and thumb movements during day-to-day activities (Sauermann et al, 2005;Simone and Kamper, 2005), timing, velocity and force of finger tapping (Aparicio et al, 2005;Bazner et al, 2005;Kandori et al, 2004;Yahalom et al, 2004), and kinematics of wrist flexion-extension (Byblow et al, 2003), handwriting (Caligiuri et al, 2006) gross arm movement (Byblow et al, 2002;Rand et al, 2002), and reach-to-grasp movements (Hosseini et al, 2000;Jackson et al, 2000;Rand et al, 2006;Tunik et al, 2004;Wenzelburger et al, 2000;Whishaw et al, 2002). Portable and convenient methods measure single aspects of motor function, such as finger bending movements (Sauermann et al, 2005;Simone and Kamper, 2005).…”
Section: Introductionmentioning
confidence: 99%